Knowledge and compliance towards standard precautions among pediatric nurses at Hospital Universiti Sains Malaysia (Hospital USM) - Jing, Wong Jing (Universiti Sains Malaysia, 2014)
Knowledge and compliance towards SP is essential in order to prevent or reduce nosocomial infections. But sadly, the knowledge and reality of adopting SP within hospital setting was far from what was recommended and had proven to be problematic. The objectives of this descriptive cross-sectional study were to identify the level of knowledge and compliance towards SP and the factors that affected compliance towards SP among pediatric nurses at Hospital USM. It was evaluated in 66 nurses in pediatric unit (2S, 6S, 6U) which selected by using purposive sampling. Data obtained by using questionnaire modified by Luo et al. (2010) which consisted of four general information questions, 20 knowledge questions of trichromatous choices. 20 compliance items of five-point Likert scale, and ten self-efficacy items of four-point Likert Scale. The data were then processed by using SPSS version 20.0 and analyzed using descriptive statistics and Pearson Chi square test. Results obtained showed that majority of the nurses had a moderate knowledge and fair compliance towards SP. In addition, there was a significant association between clinical working experience (years) and compliance of pediatric nurses towards SP (p value= 0.012); knowledge regarding SP and compliance towards SP (p value= 0.000): and self-efficacy and compliance towards SP (p value= 0.024). Whereas, there was no significant association between working ward and compliance towards SP (/? value= 0.184) and highest nursing educational level and compliance towards SP (p value= 0.252). In a nutshell, these research findings had provided a data on knowledge and compliance level towards SP among pediatric nurses at Hospital USM. It can be a guidance to improve the knowledge and compliance towards SP among the nurses so that the nosocomial infections rate can be reduced.